The impact of different drying temperatures on black ginger slices in relation to different applications of growing media - Muhammad Nurul Azilla; Abd Rahman Zuraida; Wan Sembok Wan Zaliha (Penerbit Universiti Kebangsaan Malaysia, 2022)
Black ginger (Kaempferia parviflora Wall. Ex. Baker) or “halia hitam” in Malay has beentraditionally used as health-promoting herbs in relieving body pains, allergies, gastrointestinal disorders, and fungal infections. Recently, black ginger has increased attention from many researchers to identify its medicinal value to treat diseases. In line with that, the objective of the study is to determine the impact of drying temperatures of black ginger rhizomes slices on the different applications of growing media. The experiment was arranged in a complete randomized design with two factors viz. i) different growing media [cocopeat, cocopeat+rice husk biochar, cocopeat+palm kernel shell biochar, cocopeat+sugarcane bagasse biochar, and cocopeat+coconut shell biochar] and ii) two different drying temperature (50 °C & 75 °C) with three replications. The postharvest parameters were total phenolic compound (TPC), total antioxidant (TA), water activity (Aw), and mineral nutrients content. In conclusion, rhizomes planted in Cocopeat+600g biochar substrates such as sugarcane bagasse, rice husk, palm kernel shell, and coconut shell could be suggested as effective growing media for black ginger cultivation under fertigation system and continued with 75 °C drying temperatures without adversely affecting the postharvest quality of black ginger.